2004
DOI: 10.1038/sj.onc.1207442
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human papillomavirus type 16 E6 and E7 oncoproteins in primary foreskin keratinocytes is sufficient to alter the expression of angiogenic factors

Abstract: Human papillomavirus (HPV) 16 is involved in causing cervical cancer. The E6 and E7 proteins of HPV 16 immortalize human keratinocytes and this is due, at least in part, to inactivation of the tumor suppressor proteins p53 and pRB. These tumor suppressor proteins also regulate the expression of pro-and antiangiogenic factors by cells. For this reason, experiments were conducted to determine whether the expression of E6 and E7 in primary keratinocytes alters the phenotype of these cells such that they express d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 50 publications
6
92
1
1
Order By: Relevance
“…A few studies have shown that HPV E6/E7 could regulate VEGF expression. [36][37][38] However, the current result indicates that VEGF may also modulate HPV E7 expression.…”
Section: Short-lived Rnai In Hela Cellscontrasting
confidence: 43%
See 1 more Smart Citation
“…A few studies have shown that HPV E6/E7 could regulate VEGF expression. [36][37][38] However, the current result indicates that VEGF may also modulate HPV E7 expression.…”
Section: Short-lived Rnai In Hela Cellscontrasting
confidence: 43%
“…46 It is also known that expression of HPV 16 E6/E7 in human primary keratinocytes increased the VEGF level in these cells. 38 These reports suggest that there is a relationship between oncogene E6/E7 and angiogenesis factor VEGF with the former modulating the expression of the latter. However, in this study, we showed that silencing VEGF could also affect E7 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to oropharyngeal cancer, which is induced by repeated alcohol and tobacco exposure and is characterized by mutational loss of p16 and p53 genes, TP53 mutation and further down-regulation of CDKN2A (30)(31)(32)(33), leading to uncontrolled cellular growth in up to 80% of HNSCC. The tumor suppressor gene p53 positively regulates the expression of angiogenic inhibitors and inhibits pro-angiogenic factors (34)(35)(36).…”
Section: Chemotherapeutic Alteration Of Vegf-/pdgf-and Pdgf-rα/β Exprmentioning
confidence: 99%
“…Among the most studied pro-angiogenic factors, VEGF is consistently overexpressed in cervical neoplastic lesions (77). Overexpression of E6 is associated to higher production of VEGF in cervical cancer (22,77). Studies using transgenic mice as well as samples of human cervical tissue suggest that both E6 and E7, besides hypoxia, can stimulate VEGF production (78,79).…”
Section: Intracellular Signaling Kinasesmentioning
confidence: 99%
“…In contrast, expression of the anti-angiogenic factors trombospondin (TSP)-1 and 2 were decreased in cells infected by HPV. It demonstrates that cervical cancer expression of HPV-16 integrated genes is able to contribute to a pro-angiogenic phenotype (referred as angiogenic switch) that might support tumor growth and invasion (22,74,80).…”
Section: Intracellular Signaling Kinasesmentioning
confidence: 99%